The rise of independent administrative authorities in Turkey: A close look on sources, successes and challenges of this new institutional transformation - Yavuz Göktaylar (International Telecommunications Society (ITS), 2011)
Turkey has experienced important institutional transformation during the last decades. In particular, it has started with liberal policies of early 1980s. Turkey has abandoned the import substitution policies after a serious balance of payment crisis. Foreign trade regime has been liberalized and export oriented development strategy has been adopted. The main goal has been to create a market based economy integrated with world markets. However, this first wave of institutional change is far from adequate. On the contrary, inadequate regulatory framework at financial sector and widespread corruption as well as bad macroeconomic management has led to crises between 1990 and 2001. Thus, the institutional change towards regulatory state is triggered with those economic crises. In response to these economic crises and the external pressure of global institutions like the IMF, significant legal changes such as liberalization in utilities sectors and restructuring of banking sector have been realized and some independent regulatory authorities have been set up. The Competition Authority was established in 1994 as part of the Custom Union agreement with the European Union (EU). The Banking Regulation and Supervision Agency was established in 1999 to improve the effectiveness of regulation and supervision and to establish an independent decision-making mechanism for the banking sector. The legal infrastructure for the Central Bank's independence was established by amending some articles of the Banking Law in 2001. Telecommunications Authority and Energy Market Regulatory Authority were set up in 2001 prior to liberalization of communications and electricity generation and distribution markets. The implicit logic of all this so-called structural reforms is to create and enhance the market based economy and the associated rationalization of public management in line with it. The Central Bank's independence from the political authorities that is perceived as a vital guarantee for prevention of irresponsible monetary policies, liberalization of electricity, gas, telecommunications and aviation sectors, privatization of large state monopolies at those utilities sector including Turk Telekom, building independent regulatory authorities, …etc are among some of the important changes of this new institutional era. In this paper, I try to discuss the questions why these significant institutional changes have occurred and what the promises realized and shortfalls of these authorities during the last decade in Turkey by conducting a literature survey. I think that after the introduction of second wave of institutional change, macroeconomic stability has substantially improved by creating a new institutional environment based on market mechanism and state as a regulator. Institutional change has been seemed to be successful for avoiding crisis in spite of the global financial crisis. The robustness of banking sector due to the restructuring is crucial for avoiding crises. On the other hand, new institutional environment is far from perfect. There are some serious risks and deficits. First, legal ambiguities between regulatory agencies may create power struggles and inefficiency. Secondly, having independent regularity authorities and new laws alone does not mean a guarantee for expected effective results. Finally, political class in Turkey is a myopic behaviour and their understanding has very serious short comings. Especially, I argue that the political commitment to support those independent administrative authorities by political elites is limited. I believe that the role of independent administrative authorities and the reorganization of Turkish traditional state structure towards regulatory state will continue to be debated in near future.
Keywords: 330